Impact of IUFD on Mothers in Developing Countries: A Rapid Review - Jesus, Helena Marques de; Pratiwi, Cesa Septiana (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background: Losing a baby to IUFD has a profound emotional impact on mothers. This not only affects their mental health and quality of life but also emphasizes the importance of psychological support in the recovery process. Objectives: This review aims to explore recent evidence on the biological, psychological, and social impact of intrauterine fetal death (IUFD) on mothers in developing countries. Methods: This review involved searching databases from 2015 to 2023 through sources such as PubMed, ScienceDirect, and Wiley, as well as search engines such as Google Scholar and Research Rabbit. Articles were selected with the help of Mendeley and evaluated using the JBI Critical Appraisal Guidelines for Qualitative Research. Of the 314 articles found, 5 articles met the inclusion criteria. Results: This review identified three main themes: biological impact (disturbing physical changes and danger warning signs), psychological impact (mothers' emotional responses), and social impact (moral support, negative stigma, health workers' misbehavior, and the need for better social protection). Conclusions: To provide adequate emotional support as well as clear and comprehensive information about the causes and next steps after fetal death, health workers need to be equipped with skills and knowledge. In situations that require difficult information delivery, midwives also need to have the sensitivity and skills to help parents manage and respond appropriately to their emotions.ABSTRACT Background: Losing a baby to IUFD has a profound emotional impact on mothers. This not only affects their mental health and quality of life but also emphasizes the importance of psychological support in the recovery process. Objectives: This review aims to explore recent evidence on the biological, psychological, and social impact of intrauterine fetal death (IUFD) on mothers in developing countries. Methods: This review involved searching databases from 2015 to 2023 through sources such as PubMed, ScienceDirect, and Wiley, as well as search engines such as Google Scholar and Research Rabbit. Articles were selected with the help of Mendeley and evaluated using the JBI Critical Appraisal Guidelines for Qualitative Research. Of the 314 articles found, 5 articles met the inclusion criteria. Results: This review identified three main themes: biological impact (disturbing physical changes and danger warning signs), psychological impact (mothers' emotional responses), and social impact (moral support, negative stigma, health workers' misbehavior, and the need for better social protection). Conclusions: To provide adequate emotional support as well as clear and comprehensive information about the causes and next steps after fetal death, health workers need to be equipped with skills and knowledge. In situations that require difficult information delivery, midwives also need to have the sensitivity and skills to help parents manage and respond appropriately to their emotions.